Assessing the impact of COVID-19 on renal health in recovered patients: a multi-center longitudinal study - Laura Garazhayeva; Abduzhappar Gaipov; Almagul Kauysheva (National Scientific Medical Center, 2024)
The coronavirus pandemic of 2019 has become a global health problem. This article presents an analysis of the scientific literature focusing on the pathogenetic and clinical parallels between the kidneys and SARS-CoV-2, as well as the state of kidney health in patients who have recovered from treatment. The goal is to analyze the effects of COVID-19 on kidney health in recovered patients amid an unprecedented flow of scientific data. To achieve this goal, we analysed scientific databases to study the impact of COVID-19 on kidney health in recovered patients. The majority of patients infected with coronavirus had kidney damage, comorbidities, and insufficiency of many organs. Deterioration of kidney function after COVID-19 is observed not only in patients with urological diseases, but also in those patients who have not previously had kidney problems. Despite the fact that nephrologists have developed rapid response methods and defined emergency tactics for the management of patients with kidney damage in COVID-19, cases of kidney disease continue to increase, and the percentage of patients in intensive care units is increasing. For better medical outcomes, careful monitoring of renal function and early laboratory diagnostics to determine biochemical markers, both serum, and urine, in patients with COVID-19 and continuous monitoring of these indicators after recovery are recommended.